ESTIMATION OF MOSCOVIAN STAGE WEST-SHEBELYNSKA AREA CLASTIC SEDIMENTARY ROCK RESERVOIR PROPERTIES USING LABORATORY PETROPHYSICAL DATA - Bezrodna І.; Antoniuk, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The research focuses on the analysis of petrophysical properties and parameters, and estimation of pore space structure of moscovian stage rocks of 701 Bis well in the West-Shebelynska area (depth interval 4929-5380 m) to estimate their reservoir properties. Laboratory measurements involved examination of the porosity, permeability, and fluid saturation, electrical and acoustic properties of dry and saturated rock samples. The analyses are performed in the petrophysical laboratory of the Institute of Geology. Statistical analysis of petrophysical data allowed classifying core samples into groups and separating reservoir rocks. The correlations between petrophysical parameters for the isolated group of samples are established. Assessment of void space structure is made by original method of inversion of acoustic studies in space pore structures. The concentration of different types of voids (intergranular, secondary and fracture) in total porosity of rocks is estimated based on petrophysical data (bulk density, open porosity coefficient and P-wave velocity). Fracture voids are present in all samples of the selected group and amount to 0,47-0,91%. Secondary porosity prevails over intergranular voids values in all samples, except for two, and is 1.2-7.75%. The examination of petrophysical properties and determination of the space pore structure of West-Shebelynska area samples showed that rocks in range of 5202-5211 m are perspective compacted reservoir rocks.